The independent contribution of neighborhood disadvantage and individual-level socioeconomic position to self-reported oral health: a multilevel analysis - Turrell G, Sanders AE, Slade GD, Spencer AJ, Marcenes W. (Blackwell Synergy, 2007)
To examine the association between neighborhood disadvantage and individual-level socioeconomic position (SEP) and selfreported oral health.